1990
DOI: 10.1080/00207599008246815
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐cultural Comparisons on Psychosemantics of Icons and Graphics

Abstract: This study is to report a cross‐cultural comparison on perceptions of icons and graphics and their relationships. Data were ratings of 10 icons and 10 graphics against 21 bipolar semantic differential scales from 325 college students in three countries, Mexico, Columbia, and Japan. Cross‐cultural factor analyses resulted in the identification of four semantic (three affective and one denotative) features, three icon factors, and three graphic factors. Indigenous cultural means of these iconic and graphic facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…In our study, natural also included round, and only partially included representative. The enhanced role for round is consistent with findings that show Asians like rounder shapes (Schmitt & Simonson, 1997;Tzeng et al, 1990).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, natural also included round, and only partially included representative. The enhanced role for round is consistent with findings that show Asians like rounder shapes (Schmitt & Simonson, 1997;Tzeng et al, 1990).…”
Section: Resultssupporting
confidence: 91%
“…They further use case studies to suggest that the Bank of China's angular building evokes feelings of power but has also been associated with conflict, bad luck, and strife (Schmitt & Simonson, 1997). Similarly, Tzeng, Trung, and Rieber (1990) found that Japanese rated graphics with rounded elements to be good, beautiful, strong and powerful. Thus, angularity/roundness, ornamentalism/ simplicity and realism/abstractness will be important variables to study.…”
Section: Design Characteristics and Theorymentioning
confidence: 94%
“…In fact, the curvature effect has been primarily studied using Western populations (Corradi et al., 2019a), except for a few studies that used non-Western populations, such as in Ghana (e.g., Gómez-Puerto et al., 2018). Studies (Cho et al., 2018; Tzeng et al., 1990) have addressed cultural differences between Asians (including Japanese) and other populations, but the topics thereof were not directly relevant to the curvature effect. The present study demonstrated a preference for curved objects, albeit weak, in Asian (i.e., Japanese) observers.…”
Section: Discussionmentioning
confidence: 99%
“…Rogers and Osborne [5] found that people tend to crystallise abstract concepts in terms of concrete symbols that can be visually represented. Therefore graphic symbols are often considered as a potential universal means of communication, which can convey certain types of information more directly and immediately than words [6].…”
Section: Advantages Of Visual Representationsmentioning
confidence: 99%